Pengembangan Model Pembangkit Listrik Tenaga Picohydro Tipe Turbin Cross Flow Head Rendah - Gun Gun R Gunadi; Jusafwar; Candra Damis Widiawaty; Machfud Priyo Utomo; Ramdana Ajie Satria; Muhammad Raihan Abimanyu; Adi Syuriadi; Dianta Mustofa Kamal; Rosidi (Infotekmesin, 2022)
The provision of food, energy supply, and the provision of information are The food provision, energy supply, and information delivery are controlled to improve people's welfare. In 2011, the national electricity production by PLN was 11% new and renewable energy. 6% hydropower and 5% geothermal. PLN plans the geothermal to be 13% and hydropower to be 6%. The availability of independent PhPP has been built by many communities. PhPP with a waterwheel drive provides a capacity of about 100 watts thus it is only enough for home lighting, whereas the hydro energy potential of the area is quite abundant. The development that has been carried out has several weaknesses; PhPP plump turbine type requires a high head which becomes a constraint for agricultural irrigation, in the other hand PhPP waterwheel type has low efficiency. The research was conducted to develop PhPP low head cross-flow turbine type, which is more efficient. The development begins with the experiment of the PhPP cross-flow turbine model to optimize the ratio of the diameter and width of the runner. A preliminary case study provides experimental results for a cross-flow turbine's torque and power parameters at a flow rate of 0.053 m3/s. Changes in the turbine diameter and width ratio are optimum at a runner width of 10 cm.